Advanced techniques in logic synthesis, optimizations and applications - Khatri, Sunil P. 1965-.; Gulati, Kanupriya; SpringerLink (Online service). (New York, NY Springer New York, 2011)
Advanced Techniques in Logic Synthesis, Optimizations and Applications Edited by: Sunil P Khatri Kanupriya Gulati This book covers recent advances in the field of logic synthesis and design, including Boolean Matching, Logic Decomposition, Boolean satisfiability, Advanced Synthesis Techniques and Applications of Logic Design. All of these topics are valuable to CAD engineers working in Logic Design, Logic Optimization, and Verification. Engineers seeking opportunities for optimizing VLSI integrated circuits will find this book as an invaluable reference, since there is no existing book that covers this material in a systematic fashion. Covers the latest research in the areas of Boolean Matching, Logic Decomposition, Boolean Satisfiability Serves as a single-source reference to key topics in logic synthesis, otherwise only available in disparate publications; Describes a range of synthesis techniques and Applications of logic design.
Electronic reproduction.
Keywords: Logic circuits -- Computer-aided design; Logic design -- Data processing; electronic books